Doprowadż wyrażenia do najprostrzej postaci i oblicz ich wartośći liczbowe dla podanych obok liczb\

a)
2x +(2x-y)-(x+2y)+(-2x-y) dla x= -3 dla y= -2

b)
2x-(-5x+2y-z)+(-x+y+2z) dla x=3 y=1

c)(2a + 3b) +(-3a+b+2)-(4a - b -3) dla a=4 b= -4

pilne !

2

Odpowiedzi

2010-01-14T13:38:12+01:00
A) 2x+2x-y-x-2y-2x+y= x-2y=3-2=1
b)2x+5x-2y+z-x+y+2z= 6x-y+3z=18-1+3z=17+3z
c)2a+3b-3a+b+2-4a+b+3=-5a+5b+5=-20-20+5=-35
2010-01-14T13:40:51+01:00
2x +(2x-y)-(x+2y)+(-2x-y) dla x= -3 dla y= -2
=2x + 2x - y -x -2y -2x +y =
= x -2y
= (-3) -2*(-2) = (-3) + 4 = 1

b)
2x-(-5x+2y-z)+(-x+y+2z) dla x=3 y=1
=2x +5x - 2y + z -x + y + 2z=
= 6x -y + 3z
= 6*3 - 1 + 3z
= 18 -1 + 3z
= 17 +3z


c)
(2a + 3b) +(-3a+b+2)-(4a - b -3) dla a=4 b= -4
2a + 3b -3a + b +2 -4a +b + 3=
= -5a + 5b + 5
= (-5)*4 + 5*(-4) +5=
= -20 -20 + 5=
= -40 + 5=
= -35